Investigation of Novel Biomarkers for Pancreatic Cancer - Emmanouilidi, Aikaterini (Curtin University, 2019)
Pancreatic ductal adenocarcinoma (PDAC) is a disease with dismal prognosis and an 8% chance of survival 5 years post-diagnosis, and is very challenging diagnostically and therapeutically. Exosomes are nanometre-sized vesicles known to mediate cancer spread and chemotherapy resistance. In this study, a comprehensive proteomic and lipidomic analysis of PDAC-derived exosomes has been performed. A specific enrichment of key signalling proteins and lipids with a potential role in PDAC progression has been identified.